Antioxidant and Antibacterial Activity of Suaeda maritima from Karangantu Waters, Serang-Indonesia - Afifah, Rufnia Ayu; Nurbani, Siti Zachro; Yusup, Muhamad; Sayuti, Mohammad (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2024)
Suaeda maritima or locally called Alur in Indonesia is a water-based plant that has high nutritional content and commonly consumed as fresh vegetables or urap. Therefore, this study aimed to determine the content of phytochemicals, antioxidants and antibacterial activities in Suaeda maritima extracts. Fresh Suaeda maritima was analyzed for its proximate content then it was dried by hot air dryer at 40°C until the moisture content reached ≤10%. The dried Suaeda maritima was extracted by maceration and ultrasonication method using three different solvents, namely methanol, ethanol, acetone. The extracts then were analyzed for the phytochemical compounds, total phenolics content, antioxidant activity (FRAP methods), and antibacterial activity. The results showed that fresh Suaeda maritima comprised of moisture 86.74±0.58%; ash 2.76±0.17%; protein 1.08±0.33%, lipid 0.47±0.11%; and carbohydrate 8.94±0.82%. It was also revealed that overall extracts, both in maceration and ultrasonication methods, comprised of alkaloids, flavonoids, phenolics, steroids, tannins, and saponins. The ethanol extract by the maceration methods had the highest total phenolic contents among the other extracts, which was 6.20±0.27 mg GAE g-1 (P0.05). The highest antioxidant activity was 85.04±4.01 mM FeSO4/g also found in ethanol extract by maceration method. It was proven that there was high relationship between the total phenolic content and antioxidant activity, which the R2 was 0.9242. However, the antibacterial activity for inhibiting Escherichia coli and Staphylococcus aureus on Suaeda maritima was categorized as weak due to its clear zone was 5 mm. In conclusion, Suaeda maritima extract would be potential as natural source of antioxidant.